Feasibility, efficacy, and safety of radiofrequency catheter ablation for cardiac arrhythmias: A twelve-year experience in Thailand - Apiyasawat,S. (Medical Association of Thailand, 2015)
Background: Radiofrequency catheter ablation (RFCA) is widely accepted as a curative treatment for many types of cardiac arrhythmias. Material and Method: The authors retrospectively reviewed 1,193 cases (mean age 45, 41% male) performed in the electrophysiology laboratory at Ramathibodi Hospital from 1996 to 2007. Success rate, recurrence rate and complications were analyzed. Results: Ablations of atrioventricular nodal reentrant tachycardia (AVNRT, 428 cases, 35.9%) and atrioventricular reentrant tachycardia (AVRT, 346 cases, 29%) were the most common procedures. The overall success rate and recurrence rate of RFCA were 88.8% and 6.1% respectively. Complications occurred in 50 patients (4.2%) with 1 death (0.08%). RFCA of AVNRT or AVRT rather than other arrhythmias (Odd ratio 11.46, 95% confidence interval 8.14-16.15, p < 0.001) and adult rather than pediatric patients (Odd ratio for age 1.007, 95% confidence interval 1.003-1.011, p < 0.001) were independent predictors for successful RFCA. Conclusion: RFCA of cardiac arrhythmia in our institution is safe and effective.